Intracranial tumours during the first two years of life: presenting features. Issue 4 (October 1995) - Gordon, G S; Wallace, S J; Neal, J W
Abstract : Between 1979 and 1994, 21 children (nine females, 12 males) with intracranial tumours diagnosed before the age of 2 years (range 2-23 months) were treated at the University Hospital of Wales. The commonest presenting symptoms were vomiting (n = 9) and unsteadiness (n = 8); the commonest presenting sign was enlarged occipitofrontal circumference (> 97th centile in 16 and > 90th centile in a further two). In five cases with signs of raised intracranial pressure, meningitis was the clinical diagnosis, and a lumbar puncture was performed. For cases with long delays in diagnosis, multiple other disorders had been considered and the significance of head enlargement had not been recognised. In very early childhood, intracranial tumours are uncommon and can mimic other disorders, especially meningitis. Early neuroimaging is advised when a child presents with recent onset of neurological symptoms and a disproportionately large head.